Electrolyte Measures to Prevent Polysulfide Shuttle in Lithium‐Sulfur Batteries. Issue 7 (18th May 2022) - Di Donato, Graziano; Ates, Tugce; Adenusi, Henry; Varzi, Alberto; Navarra, Maria Assunta; Passerini, Stefano
Abstract: Lithium‐sulfur (Li−S) batteries are recognized as one of the most promising technologies with the potential to become the next‐generation batteries. However, to ensure Li−S batteries reach commercialization, complex challenges remain, among which the tailoring of an appropriate electrolyte is the most important. This review discusses the role of electrolytes in Li−S batteries, focusing on the main issues and solutions for the shuttle mechanism of polysulfides and the instability of the interface with lithium metal. Herein, we present a background on Li−S chemistry followed by the state‐of‐the‐art electrolytes highlighting the different strategies undertaken with liquid and solid electrolytes. Abstract : The management of lithium polysulfides is essential for the commercialization of lithium‐sulfur batteries (LSBs). In the conversion chemistry of LSBs the electrolyte plays a key role to enhance the typical specific energies of lithium‐ion batteries. The type of electrolyte, composition, amount, and interactions with lithium are all factors that must be considered in the development of viable electrolytes for practical LSBs.